Photocatalytic Degradation of Gentian Violet Using BaxSr1-xFe0.5Co0.5O3-d - Huang, Xianghong; Qiao, Jun; Zhang, Qianfeng (Asian Journal of Chemistry, 2014)
Perovskite oxides BaxSr1-xFe0.5Co0.5O3-d (x = 0.2, 0.4) were synthesized by citrate method. The structures and the morphology of the prepared samples were characterized by X-ray diffraction and scanning electron microscopy. The photocatalytic degradation property of Gentian violet in aqueous solution was investigated using BaxSr1-xFe0.5Co0.5O3-d as the photocatalysts. The effects of irradiation time, catalyst dose, initial concentration and pH value on the degradation were explored systematically under the irradiation of a 400 W high pressure mercury lamp. The optimum reacted conditions were that irradiation time was 60 and 80 min, catalyst dose 0.2 and 0.22 g in 100 mL 10 mg/L Gentian violet solution using Ba0.2Sr0.8Fe0.5Co0.5O3-d and Ba0.4Sr0.6Fe0.5Co0.5O3-d, respectively, initial concentration and pH value were Gentian violet 5 mg/L and 3.08 for both photocatalysts.